Japanese demon lore : oni, from ancient times to the present - Reider, Noriko T. (UPCC book collections on Project MUSE., 2010)
Oni, ubiquitous supernatural figures in Japanese literature, lore, art, and religion, usually appear as demons or ogres. Characteristically threatening, monstrous creatures with ugly features and fearful habits, including cannibalism, they also can be harbingers of prosperity, beautiful and sexual, and especially in modern contexts, even cute and lovable. There has been much ambiguity in their character and identity over their long history. Usually male, their female manifestations convey distinctively gendered social and cultural meanings. Oni appear frequently in various arts and media.